Histopathological Profile of Ovarian Masses - Sherpa, Palzum; Baral, Reetu (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: The aim of this study was to evaluate the incidence of neoplastic as well as non-neoplastic ovarian lesions and to find out the frequency and age distribution of benign and malignant ovarian neoplasms. Methods: A retrospective cross sectional study on a series of cases was performed in the Department of Pathology, Patan Academy of Health Sciences, Patan Hospital, Lalitpur, Nepal from April 2011 to March 2016. Data from the histopathology database were analyzed using SPSS version 16.0. Results: During the study period, surgical specimens of 528 ovarian masses were received at our institution. Among them, 399 cases (76%) were neoplasms and 129 cases (24%) were non-neoplastic lesions. Benign, borderline and malignant neoplasms were 89.7%, 1.8% and 8.5% respectively. Benign neoplasms were more common in 21-30 years and malignant in 41-50 years age group. There were 156 (39.1%) surface epithelial tumors, 236 (59.1%) germ cells tumors and 6 (1.5%) sex cord stromal tumors. Mature cystic teratoma, followed by serous cystadenoma was the most frequently encountered benign tumor. Serous cystadenocarcinoma was most prevalent in the malignant group. Among the non-neoplastic masses, the most common was endometriotic cyst (55%) followed by corpus luteal cyst (29%). Conclusions: Ovarian neoplasms are more common than non-neoplastic lesions. Malignant tumors affect older women more frequently than younger women. Mature cystic teratoma was the most frequently encountered benign tumor. Serous cystadenocarcinoma was most prevalent in the malignant group. Endometriotic cyst was the most common non-neoplastic lesion.